COORDINATION CHEMISTRY OF TI(IV) IN SILICATE GLASSES AND MELTS: II. GLASSES AT AMBIENT TEMPERATURE AND PRESSURE - Farges F.; Brown G.E.; Navrotsky A.; Hao G.; Rehr J.J. (My University, 1996)
The coordination environment of Ti(IV) in a number of Ti-silicate and Ti-aluminosilicate glasses has been determined by x-ray absorption fine structure (XAFS) spectroscopy at the Ti K-edge at ambient temperature and pressure. These glasses contain 2.7-30.5 wt% TiO2 and varying amounts of Na2O, K2O, or CaO (5.0-38.7 wt%) and Al2O3 (0-11.9 wt%), and have NBO/T ratios ranging from 0.07-0.81.Quantitative analysis of the Ti XANES spectra, based on ab initio multiple-scattering calculations for a variety of Ti-containing clusters, and anharmonic analysis of the normalized XAFS oscillations suggest the presence of three types of atoms around Ti: O first neighbors, (Si, Ti)-second neighbors, and alkali third neighbors. Five-coordinated Ti, [5]Ti, is the dominant Ti species in the glasses most concentrated in Ti (> 16 wt% TiO2) and is located in distorted square pyramids ([5]TiO)O4), with one short Ti#O titanyl distance (1.67-1.70 +/- 0.03 a) and four long Ti--O distances (1.94-1.95 +/- 0.02 a). In addition, minor amounts of [4]Ti were detected, the proportion of [4]Ti increasing in the order: Na glasses < K glasses. [4]Ti is the dominant Ti species in the potassic glasses with the lowest TiO2 contents (#3-6 wt%) and highest NBO/T ratio. The relative amount of [4]Ti increases in the order: Ca glass < K glass. Finally,[6] Ti is a minor species (<20%) when detected in these glasses.The presence of Ti-(Si, Ti) correlations near 3.2-3.4 +/- 0.1 a, as in crystalline Na2([5]TiO)SiO4, is consistent with [5]TiO5 and SiO4TiO5 polyhedra sharing corners in these glasses, with Ti--O-(Si, Ti) angles of #120o-130o +/- 10o. Quantitative analysis of the Ti K-edge XANES for the K-bearing glasses suggests the presence K around Ti, in good agreement with bond-valence predictions, which indicate that [5]Ti is most likely to bond to both nonbridging oxygens (one O in short Ti#O titanyl bonds) and bridging oxygens (four O in long Ti--O bonds), thus can act as a new type of Q4 specie with one additional nonbridging oxygen. Then, we propose [5]Ti to behave simultaneously a network former and a network modifier, with the network former role dominant. Bond valence models explain why the relative proportions of [4]Ti and [5]Ti change when the type of low field strength cation or the type of network-forming cation (Si vs. P) changes in oxide glasses. These models also provide a structural basis for the study of glasses and melts at higher temperatures (see Part III of this study).